Assessing Coronary Blood Flow Physiology in the Cardiac Catheterisation Laboratory - Vijayan, Sethumadhavan; S. Barmby, David; R. Pearson, Ian; G. Davies, Andrew; B. Wheatcroft, Stephen; Sivananthan, Mohan (Current Cardiology Reviews, 2017)
Background: Contemporary management of coronary disease focuses on the treatment of stenoses in the major epicardial vessels. However, myocardial blood flow is known to be contingent on a range of factors in addition to the patency of the epicardial vessels. These include anatomical and physiological factors such as the extent of myocardium supplied by the vessel, systemic blood pressure, the natural variation in vascular tone in response to physiological needs which allows for coronary autoregulation and pathological factors such as the presence of downstream obstruction to flow due to disease of the small coronary vessels or myocardium. The assessment of clinical effectiveness and adequacy of coronary revascularisation requires the ability to comprehensively and accurately assess and measure myocardial perfusion. Conclusion: In this article, we review the current methods of evaluating coronary blood flow and myocardial perfusion in the cardiac catheterisation laboratory.
Keywords: Coronary physiology